Evaluation of the Farmers' Markets for Kids programme. Issue 18 (28th July 2016) - Dannefer, Rachel; Bryan, Erica; Osborne, Alyce; Sacks, Rachel
Abstract: Objective: To assess the impact of Farmers' Markets for Kids, a farmers' market-based, child-oriented nutrition education programme, on attitudes and behaviours related to preparing and consuming produce among child participants and their caregivers in New York City (NYC). Design: Retrospective pre-test/post-test cross-sectional survey with caregivers of children participating in Farmers' Markets for Kids classes. Setting: Four NYC farmers' markets where Farmers' Markets for Kids classes are implemented; these markets serve low-income communities. Subjects: Two hundred and twelve adult caregivers of children who participated in Farmers' Markets for Kids classes. Results: Caregivers reported that children's consumption of fruits and vegetables had increased since participating in Farmers' Markets for Kids and that their children more frequently assisted with food preparation; both of these improvements were statistically significant. Caregivers also reported significant improvements in attitudes: since participating in Farmers' Markets for Kids, their children were more willing to try new fruits and vegetables and caregivers found it easier to prepare fruits and vegetables for their children. Almost all respondents (99 %) reported purchasing more fruits and vegetables since participating in Farmers' Markets for Kids and 95 % had prepared the programme's recipes at home. Conclusions: Findings suggest that Farmers' Markets for Kids may be an effective approach for increasing produce consumption among participating children and improving related attitudes among children and caregivers. This evaluation provides support for future efforts to undertake more rigorous evaluations of such programmes.